Adolescent abstinence and unprotected sex in CyberSenga, an Internet-based HIV prevention program: randomized clinical trial of efficacy. - Michele L Ybarra; Sheana S Bull; Tonya L Prescott; Josephine D Korchmaros; David R Bangsberg; Julius P Kiwanuka (PLoS ONE, 2013)
Cost-effective, scalable programs are urgently needed in countries deeply affected by HIV.This parallel-group RCT was conducted in four secondary schools in Mbarara, Uganda. Participants were 12 years and older, reported past-year computer or Internet use, and provided informed caregiver permission and youth assent. The intervention, CyberSenga, was a five-hour online healthy sexuality program. Half of the intervention group was further randomized to receive a booster at four-months post-intervention. The control arm received 'treatment as usual' (i.e., school-delivered sexuality programming). The main outcome measures were: 1) condom use and 2) abstinence in the past three months at six-months' post-intervention. Secondary outcomes were: 1) condom use and 2) abstinence at three-month's post-intervention; and 6-month outcomes by booster exposure. Analyses were intention to treat.All 416 eligible youth were invited to participate, 88% (n = 366) of whom enrolled. Participants were randomized to the intervention (n = 183) or control (n = 183) arm; 91 intervention participants were further randomized to the booster. No statistically significant results were noted among the main outcomes. Among the secondary outcomes: At three-month follow-up, trends suggested that intervention participants (81%) were more likely to be abstinent than control participants (74%; p = 0.08), and this was particularly true among youth who were abstinent at baseline (88% vs. 77%; p = 0.02). At six-month follow-up, those in the booster group (80%) reported higher rates of abstinence than youth in the intervention, no booster (57%) and control (55%) groups (p = 0.15); they also reported lower rates of unprotected sex (5%) compared to youth in the intervention, no booster (24%) and control (21%) groups (p = 0.21) among youth sexually active at baseline.The CyberSenga program may affect HIV preventive behavior among abstinent youth in the short term and, with the booster, may also promote HIV preventive behavior among sexually active youth in the longer term.NCT00906178.